2016
DOI: 10.1111/isj.12103
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging virtual business model innovation: a framework for designing business model development tools

Abstract: This paper presents a framework for developing tool support for the design and management of new business models. Existing IT tools supporting the process of designing, innovating, and evaluating a company's business model are currently not leveraging the full potential of tool support, because they do not make use of theoretical and empirical knowledge around business model development. Against this backdrop, we analyze existing knowledge on business model design and management, resulting in a first systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 80 publications
0
51
0
1
Order By: Relevance
“…Software-based tools for business model development are a new class of software that has been credited with great potential for supporting users in innovating business models (e.g., Ebel et al, 2016;Osterwalder & Pigneur, 2013;Veit et al, 2014). The potential of software-based tools to support creative tasks has been recognized in the information systems discipline for the purpose of developing not only business models, but also strategies and products (e.g., Schneider & Spieth, 2013;Kawakami et al, 2015;Kaplan, 2011).…”
Section: Business Model Development Tools (Bmdts)mentioning
confidence: 99%
See 2 more Smart Citations
“…Software-based tools for business model development are a new class of software that has been credited with great potential for supporting users in innovating business models (e.g., Ebel et al, 2016;Osterwalder & Pigneur, 2013;Veit et al, 2014). The potential of software-based tools to support creative tasks has been recognized in the information systems discipline for the purpose of developing not only business models, but also strategies and products (e.g., Schneider & Spieth, 2013;Kawakami et al, 2015;Kaplan, 2011).…”
Section: Business Model Development Tools (Bmdts)mentioning
confidence: 99%
“…Despite the importance of idea generation for business model innovation, prior research has largely neglected it (Schneider & Spieth, 2013), and in particular the creative aspect of business model idea generation is little understood (Martins et al, 2015). Thus, business model innovation is a cognitive as well as a creative task (Ebel et al, 2016;Eppler et al, 2011) and prior research has found that such tasks can benefit from being supported by software tools (e.g., Hender et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peters et al [21] also propose a morphological box for the analysis, description, and classification of IT-enabled service BMs. Regarding BM management process, IS research is particularly interested in frameworks for BM management [13], IT support for BM design and management [22], and the design of IT platform BMs [23].…”
Section: State-of-the-art: the Business Model Conceptmentioning
confidence: 99%
“…This novel role has been recently reflected on the notion of businessmodel-based management (BMBM) [12] as a way of developing management methods that draw on the BM concept to holistically plan, organize, direct, and control the structure and dynamics of an organization [13]. While organizations mainly leverage BMs in an innovation context to ensure the economic viability of new products and services [1,22], the BM concept's potential to manage organizations over their entire life cycle [28] is widely ignored. As such, BMBM aims to adopt the BM concept in management methods to eventually guide practitioners in constructing and maintaining their organizations' business logic [12,13].…”
Section: State-of-the-art: the Business Model Conceptmentioning
confidence: 99%